Growing Season Energy and CO2 Fluxes over a Larch Forest Tundra Ecosystem in Siberia (Arctic Data Center, 2016)
This data set includes eddy covariance measurements of carbon and energy fluxes over a larch forest-tundra ecosystem near the latitudinal treeline, collected near Cherskii, Siberia, in summer 2001. A series of basic micrometeorological variables were also measured, including vertical profiles of air temperature and relative humidity, wind speed, net radiation, albedo, incoming and outgoing long wave radiation, wind direction, and precipitation. At each site four soil micro sites were also selected to measure soil temperature at 5 depths, soil heat flux, and soil moisture.